ASSESSMENT OF THE RESISTANCE PROFILE OF Escherichia coli TO ANTIBIOTICS FROM AGRICULTURAL MICROBASIN LOCATED IN THE NORTHWEST OF THE STATE OF RIO GRANDE DO SUL, BRAZIL - Flach, Kauane; Rosa, Genesio Mario da; Bones, Ubiratan Alegransi; Soriani, Hilda Hildebrand (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2024)
Antimicrobial resistance acquired by bacteria is a central topic in discussions about the environment and emerging waterborne diseases. Therefore, the objective of this study was to determine the in vitro bacterial sensitivity, specifically of Escherichia coli (E. coli) strains previously isolated from Lajeado Pardo, located in the municipality of Frederico Westphalen, in the northwest region of Rio Grande do Sul state, Brazil. Five antimicrobials were tested using the Antimicrobial Sensitivity Test (AST) on isolated bacteria samples and evaluated according to their resistance (R) and sensitivity (S) profiles: ampicillin (AMP), amoxicillin-clavulanate (AMC), gentamicin (GEN), chloramphenicol (CHLO), and ciprofloxacin (CIP). The analysis of the selective isolation media (LSB, Colilert, and EC) showed statistically significant differences among them (p